Case Report: Primary hepatic neuroendocrine tumor: two cases report with literature review - Tang, Yongsheng; Chen, Xianyu; Lu, Xu; Yuan, Zenan; Yang, Yang; Qiu, Chunhui; Li, Hua (Frontiers in Oncology, 2023)
Abstract Background & Aims: Primary hepatic neuroendocrine tumors (PHNETs) are rare malignant liver tumors that present diagnostic challenges owing to their rarity and absence of specific clinical features. This study aimed to investigate the characteristics of this rare liver tumor to enhance our understanding of the disease, improve diagnostic accuracy, and explore standardized diagnostic and treatment approaches. Case description: During physical examination, two elderly women, aged 64 and 74 years, were found to have liver masses. 18F-FDG Positron Emission Tomography-Computed Tomography (18F-FDG PET-CT) and Ga68-DOTATATE PET-CT scans of both individuals revealed multiple liver masses that were initially suspected to be hepatic neuroendocrine tumors. Subsequent puncture pathology confirmed the diagnosis of neuroendocrine tumors. Furthermore, in Case 1, the tumor was also detected by 18F-FDG PET-CT in the lung, suggesting a metastatic tumor, in conjunction with liver immunohistochemistry and imaging findings. Laboratory tests revealed no significant abnormalities in liver function or autoimmune liver disease indicators, and there was no evidence of viral hepatitis infection. However, partial hepatectomy was not indicated for cases with distant metastasis or multiple space-occupying lesions. Individualized treatment approaches have been developed for such situations. A large portion of the tumor underwent Transarterial Embolization (TAE), and targeted combination chemotherapy or endocrine therapy was administered based on the pathological results. During regular follow-ups a 13 and 12 months, the tumor remained stable. The patients’ quality of life was good, and their psychological well-being was healthy. They led active lifestyles, demonstrated a thorough understanding of their disease and its progression, and actively cooperated during the follow-up process. Conclusion: Our findings suggest that a combination of serological, radiological, and immunohistochemical examinations can aid in the diagnosis of PHNET. In addition, we determined that TAE combined with drug therapy could be an effective method for controlling PHNET progression. Regular postoperative follow-ups are important for monitoring the prognosis and tumor progression status of patients with PHNET.